2018
DOI: 10.1111/iej.12990
|View full text |Cite
|
Sign up to set email alerts
|

Impact of root canal preparation performed by ProTaper Next or Reciproc on the quality of life of patients: a randomized clinical trial

Abstract: The two root canal preparation systems exerted a similar impact on quality of life. Postoperative pain was correlated with impact on quality of life, affecting chewing function, self-consciousness and stress. Thus, it is important for dentists to provide care capable of preventing or treating the negative consequences of such therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 30 publications
1
18
1
Order By: Relevance
“…Another limitation of the present study is that sample calculation was performed for the main outcome (reduction in periapical index) of a large trial (Figueiredo et al 2020), but not for OHRQoL. A prior similar study comparing changes on OHIP scores after the root canal treatment using either rotary or reciprocating files performed a sample size calculation for this outcome, and only 61 participants were included in that trial (Oliveira et al 2019). Therefore, the number of participants included in the present trial was almost two-fold that from the former trial.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Another limitation of the present study is that sample calculation was performed for the main outcome (reduction in periapical index) of a large trial (Figueiredo et al 2020), but not for OHRQoL. A prior similar study comparing changes on OHIP scores after the root canal treatment using either rotary or reciprocating files performed a sample size calculation for this outcome, and only 61 participants were included in that trial (Oliveira et al 2019). Therefore, the number of participants included in the present trial was almost two-fold that from the former trial.…”
Section: Discussionmentioning
confidence: 93%
“…1 year). Two previous studies investigated the short-term impact of reciprocating systems on OHRQoL, but these evaluations were limited to assess OHRQoL changes 24 h (Oliveira et al 2019) or 14 days (Bartols et al 2016) after treatment ended. These studies found a positive impact of reciprocating systems on OHRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, it is fundamental to avoid an undesirable extrusion of debris in the periradicular tissues that can be associated with the induction of inflammation and delayed periapical healing [ 19 , 20 ]. Furthermore, apical extrusion is one of the most important factors associated with postoperative pain that seems to be related to the instrumentation technique [ 21 ]; hence, its evaluation is considered relevant from a clinical point of view.…”
Section: Discussionmentioning
confidence: 99%
“…The latter aspect, apical debris extrusion, is claimed to exert a clinically relevant impact on post-endodontic pain and thus on quality of life of patients after nonsurgical root canal treatment [5][6][7][8]. During the procedure of root canal preparation, pulp tissue remnants, dentine chips, microorganisms, and solutions used for canal irrigation may be extruded apically into the periradicular tissues [4,9].…”
Section: Introductionmentioning
confidence: 99%